Intertextuality With Folk Proverbs In Naguib Mahfouz's Novel Cairo Modern - Mohd Azizul Rahman bin Zabidin; Ebrahim Mohammad Ahmad Eldesoky; Ashraf Hasan Muhammad Hasan; Lubna Abdul Rahman; Nashwa Mohamed Mohamed Elsayed; Abdul Ghani bin Md Din (Human Resource Management Academic Research Society, 2024)
Indexed by ERA